Maturidade do ovário no cascudo Hypostomus strigaticeps (Siluriformes, Loriicaridae) - Takahashi, Erico Luis Hoshiba; Goitein, Roberto; Okada Nakaghi, Laura Satiko (Universidade Estadual de Maringa, 2008)
This work studied the ovarian development of the armored catfish Hypostomus strigaticeps. Between July 2002 and June 2005, 332 females were collected monthly from the Corumbatai River, São Paulo State [long dash] Brazil. The ovaries were processed using routine histological techniques [long dash] paraffin inclusion and 5 pm thick sections stained in hematoxylin-cosin. Six types of oocytes were observed: Chromatin-nucleolus, Perinncleolar, Cortical-alveolus, Vitellogenic, Ripe and Atresic. Four maturity stages were created based on macroscopic and microscopic morphological observations, as well as on analysis of the gonadossomatic index (GSI): Rest, Maturation, Ripe and Spawned.
Ovarian organization and maturity stages of armored catfish Hypostomus strigaticeps (Siluriformes, Loriicaridae).